Identification of a Genetic Variant Common to Moyamoya Disease and Intracranial Major Artery Stenosis/Occlusion - Miyawaki, Satoru; Imai, Hideaki; Takayanagi, Shunsaku; Mukasa, Akitake; Nakatomi, Hirofumi; Saito, Nobuhito (Stroke (1970), 2012)
The c.14576G>A variant in ring finger protein 213 (RNF213) was recently identified as a susceptibility gene variant for moyamoya disease (MMD). The occurrence of c.14576G>A variant was evaluated in patients with intracranial major artery stenosis/occlusion (ICASO) without signs of MMD (non-MMD ICASO), as well as in patients with MMD and other cerebrovascular diseases as controls. This single-hospital-based case-control study was completed in 7 months (from October 2011-April 2012) at Department of Neurosurgery, The University of Tokyo Hospital. The occurrence of c.14576G>A variant was analyzed in 41 patients with non-MMD ICASO, in 48 with MMD, in 21 with cervical disease, in 61 with cerebral aneurysm, and in 25 normal subjects. Nine of 41 patients (21.9%) with non-MMD ICASO and 41 of 48 (85.4%) with MMD had the c.14576G>A variant. One of 61 patients (1.6%) with cerebral aneurysm and no patients with cervical disease or normal subjects had the variant. Comparison of each phenotype group with the normal subjects showed that presence of c.14576G>A variant had significant associations with MMD (odds ratio [OR], 292.8; 95% confidence interval [CI], 15.4-5153.0; P<0.0001) and with non-MMD ICASO (OR, 14.9; 95% CI, 0.82-268.4; P=0.01), but no association with either cerebral aneurysm (OR, 1.2; 95% CI, 0.04-32.0; P=1.00) or cervical disease (OR, 1.1; 95% CI, 0.02-62.3; P=1.00). The present study indicates that a particular subset of Japanese patients with non-MMD ICASO has a genetic variant associated with MMD. Therefore, we propose the existence of a new entity of ICASO caused by the c.14576G>A variant in RNF213.